OPTIMASI MASSA KATUP LIMBAH POMPA HYDRAM TERPASANG DI WILAYAH MUNDUK GUNUNG DESA PETANG - Suarda, M.; Suaniti, N.M.; Sucipta, M.; Suweden, N.; Dwijana, I.G.K. (Buletin Udayana Mengabdi, 2023)
This paper investigated the effect of the  mass  of the waste valve of hydraulic ram pump which has been designed and installed to  deliver  the clean water  to  the community  house  in the Munduk Gunung area, Petang Village.  P ublic facilities are still minimal. One of them is the unavailability of clean water service facilities for the community, where people still rely on rainwater or buy water tanks. In accordance with the name of the area, this residential area is located in the highlands (5 1 2 m.swl), while the available water sources are in the lowlands (410 m.swl) with an elevation difference of 1 0 2 meters. The distance from the spring to the reservoir is 600 meters through a steep cliff. Initial survey results show that the spring has a flow capacity of about 3 liters/second and a potential head of 4.5 meters. The hydraulic ram pump has been designed, built, installed and operated with funding supported through the PNBP service grant from Udayana University, the PUM A  scheme. The hydraulic ram pump performance test has been carried out on five variations of the waste valve  mass . Performance testing shows that this hydraulic ram pump reaches its optimal performance at a mass of 3.25 kg of waste valve. Under these optimal conditions, this hydraulic ram pump operates at a total efficiency of 95% with a pumping flow of 0.115 lt/sec or 9.94 m 3 /day) at a pumping elevation of 102 meters, with an economic value of up to Rp. 17,885,000 per month.  Therefore,   it is  with an investment cost of around Rp. 42,500,000 and requires almost no operational costs because it does not require fuel or electrical energy,  consequently  this hydram pump is very profitable to apply. Keywords:  Hydraulic ram pump, waste valve mass, pump performance, Munduk Gunung area, Petang village.